APPLICATION OF LASER TECHNOLOGY IN DENTAL SURGERY AND RECENT ADVANCES IN ORO-DENTAL HEALTHCARE - Dr Prafull Pujari; Dr Vrushti Ramanuj; Dr Navdeep Singh; Dr Manish Bishnoi; Dr. Aditya Kulkarni; Dr Smita Ranjan (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
The field of dental surgery has witnessed remarkable advancements in recent years, driven by the application of laser technology and innovative developments in oro-dental healthcare. This abstract provides a concise overview of the evolving landscape in dental surgery, highlighting the crucial role of laser technology and the latest trends in oro-dental healthcare. The ability to precisely target and remove infected or damaged tissue has significantly reduced patient discomfort and recovery times. Moreover, lasers in dentistry have minimized the need for traditional drilling and scalpels, making treatments more patient-friendly. Recent advances in oro-dental healthcare extend beyond technology, focusing on holistic patient care and preventive measures. The advent of tele-dentistry has enabled remote consultations and follow-ups, improving access to oral healthcare services, especially in underserved areas. This article highlights the pivotal role of laser technology in advancing dental surgery, making procedures less invasive and more patient-friendly. Furthermore, recent trends in oro-dental healthcare underscore a shift towards holistic care, preventive measures, and the integration of cutting-edge technologies.